Co-fermentation of Syrah with various additions of Viognier: Effect on colour and phenolics during winemaking and bottle ageing - Casassa, Luis Federico; Keirsey, Landon S.; Mireles, María S.; Larsen, Richard C.; Harbertson, James F. (2018)
The impetus for the study described in this article was to assess the effect of co-fermentation of Syrah and Viognier in the phenolic chemistry and colour stability of the resulting wines and to document potential benefits of this practice on wine colour, anthocyanins and tannins